A Randomized Controlled Trial Comparing 2 Multimodal Analgesic Techniques in Patients Predicted to Have Severe Pain After Cesarean Delivery. Issue 4 (December 2016) - Booth, Jessica L.; Harris, Lynnette C.; Eisenach, James C.; Pan, Peter H.
Abstract : Anesth Analg 2016;122:1114–1119 Severe acute pain following cesarean delivery is a predictor of persistent pain and depression at 2 months postpartum. Although systemic and neuraxial medications have been used to manage this pain, there are side effects, varied success rates, and little guidance on titration of opioids. Many women in the United States receive a mixture of systemic nonsteroidal anti-inflammatory drugs, opioids, and a single dose of intrathecal morphine after cesarean delivery.